Question
upstudy study bank question image url

Find an equation for the perpendicular bisector of the line segment whose endpoints are \( (-9,3) \) and \( (-3,-1) \).

Ask by Norton Rose. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation of the perpendicular bisector is \( y = \frac{3}{2}x + 10 \).

Solution

Step 1: Find the midpoint of the segment. The midpoint M of endpoints (–9, 3) and (–3, –1) is given by:   M = ((–9 + (–3))/2, (3 + (–1))/2) = (–12/2, 2/2) = (–6, 1). Step 2: Determine the slope of the segment. The slope m of the segment connecting (–9, 3) and (–3, –1) is:   m = (–1 – 3) / (–3 – (–9)) = (–4) / (6) = –2/3. Step 3: Find the slope of the perpendicular bisector. The perpendicular bisector has a slope that is the negative reciprocal of the segment's slope. Thus:   m_perp = –1/(–2/3) = 3/2. Step 4: Write the equation of the perpendicular bisector. Using the point-slope form with the midpoint (–6, 1) and slope 3/2:   y – 1 = (3/2)(x + 6). You can also express this in slope-intercept form:   y = (3/2)x + 9 + 1   y = (3/2)x + 10. So, the equation for the perpendicular bisector is:   y – 1 = (3/2)(x + 6)  or  y = (3/2)x + 10.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the equation of the perpendicular bisector, first, we calculate the midpoint of the line segment joining the endpoints \((-9, 3)\) and \((-3, -1)\). The midpoint \(M\) is given by: \[ M = \left( \frac{x_1 + x_2}{2}, \frac{y_1 + y_2}{2} \right) = \left( \frac{-9 + (-3)}{2}, \frac{3 + (-1)}{2} \right) = \left( \frac{-12}{2}, \frac{2}{2} \right) = (-6, 1). \] Next, we find the slope of the line segment. The slope \(m\) is calculated as follows: \[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{-1 - 3}{-3 - (-9)} = \frac{-4}{6} = -\frac{2}{3}. \] The slope of the perpendicular bisector is the negative reciprocal of the slope of the original line, which will be \( \frac{3}{2} \). Now, we can use the point-slope form of a line equation, \( y - y_1 = m(x - x_1) \), where \((x_1, y_1)\) is the midpoint and \(m\) is the slope of the perpendicular bisector. Substituting in our values: \[ y - 1 = \frac{3}{2}(x + 6). \] Simplifying this, we have: \[ y - 1 = \frac{3}{2}x + 9 \implies y = \frac{3}{2}x + 10. \] Thus, the equation of the perpendicular bisector is: \[ \boxed{y = \frac{3}{2}x + 10}. \]

Latest Geometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy